2001
DOI: 10.1159/000047723
|View full text |Cite
|
Sign up to set email alerts
|

Natural Coagulation Inhibitor Proteins in Young Patients with Cerebral Ischemia

Abstract: Disturbances of coagulation and fibrinolytic pathways were studied in 53 young patients with cerebral ischemia. Upon admission 26 of 53 patients had abnormality in at least one of the antithrombin-III, protein C, protein S activities or in activated protein C (APC) ratios. Three months after the first examination the majority of the previously detected abnormalities returned to normal values and the most frequent alterations were decrease in protein S activity (3 patients) and APC resistance (3 patients). Cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
1
6
0
1
Order By: Relevance
“…However other diagnosis how methylenetetrahydrofolate reductase deficiency, for example, which are rare cause of AIS was not investigated in present study. AIS in children occurs predominately in the anterior circulation and the middle cerebral artery is the vessel most affected 8,9,14,18,[22][23][24] as is confirmed in this study. Cerebral AIS occurred in an adolescent who had osteosarcoma and patent foramen ovale; prior studies showed predominance of the male sex and the presence of patent oval forame in the cases of cerebellar strokes 25 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However other diagnosis how methylenetetrahydrofolate reductase deficiency, for example, which are rare cause of AIS was not investigated in present study. AIS in children occurs predominately in the anterior circulation and the middle cerebral artery is the vessel most affected 8,9,14,18,[22][23][24] as is confirmed in this study. Cerebral AIS occurred in an adolescent who had osteosarcoma and patent foramen ovale; prior studies showed predominance of the male sex and the presence of patent oval forame in the cases of cerebellar strokes 25 .…”
Section: Discussionsupporting
confidence: 85%
“…Recent studies have not had as an objective the direct evaluation of the presence of infection in AIS, perhaps attributing to associated conditions such as dehydration and hypertension the cause of the event. Abnormalities in the natural inhibitors of coagulation, congenital or acquired, have been a current research theme and are associated to cerebral vascular disease in infancy, and its contribution to the pathology is of extreme importance in the determination of the potential risk of recurrence, the specific therapeutic and family screening 6,23,27 . In a study of AIS and of the sinovenous thrombosis, 33% of the children presented reactant anticardiolipin antibodies, 13% alteration of the antithrombin 12% of the S protein, 7% of the C protein and 9% showed resistance to activated C protein6.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained by other authors are in accordance with these. For example, Olah and coauthors in their study on 53 patients with cerebral ischemia confirm decreased fibrinolysis and increased PAI-1 values with 23 patients (28).…”
Section: Discussionmentioning
confidence: 90%
“…Seventy-three (27%) studies [17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89] included stroke or TIA as an outcome event for the purpose of a risk factor analysis. In 11 of these studies, the cerebrovascular event was part of a composite outcome which included coronary and and/or other vascular events, and in 62 studies stroke was analysed separately.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 45 studies that reported risk factor analyses for ischaemic stroke separately, only 17 studies reported risk relationships for any subtype of ischaemic stroke (table 3), of which only five studies used a formal aetiological classification: the TOAST classification [42]; Stroke Data Bank classification [48, 80], or the Villa Pini Stroke Data Bank classification [27]. One further study described in detail the subtype definitions that were used, and although they did not coincide with a previously reported classification, we categorised this as a formal classification [60]. Twelve other studies subtyped ischaemic stroke to some limited extent, but did not use any formal classification process [31, 41, 43, 46, 47, 56, 57, 61, 64, 69, 79, 88].…”
Section: Resultsmentioning
confidence: 99%